Identifikasi Dampak Limbah B3 Terhadap Area Operasional di PT PLN Nusantara Power Unit Pembangkitan 1 & 2 Nagan Raya - Mahmud Basuki; Zainuddin Zainuddin; T.M. Azis Pandria; Tya Ulfah; Arrazy Elba Ridha; Risnadi Irawan (Universitas Teuku Umar, 2026)
Hazardous and Toxic Materials (B3) waste management is an important aspect in the operation of the electricity generation industry because it has the potential to cause negative impacts on the environment and worker health. PT PLN Nusantara Power Unit Pembangkitan 1 & 2 Nagan Raya as the operator of the Steam Power Plant (PLTU) produces various types of B3 waste such as used oil, chemical packaging, used resin, used rags, and chemically contaminated waste. This study aims to identify the types and characteristics of B3 waste, analyze the B3 waste management system, and evaluate the impact of B3 waste on the operational area. The research methods used include field observation, interviews with environmental staff, documentation studies, and literature studies. The results of the study indicate that the B3 waste produced has been managed through sorting, packaging, labeling, storage in Temporary Storage Areas (TPS), and transportation by licensed third parties. However, potential impacts on the environment and occupational safety can still occur if there are leaks, delays in transportation, or non-compliance with operational procedures. Identified impacts include the potential for soil and water pollution, the risk of exposure to hazardous materials for workers, and the potential for disruption to equipment performance. This research is expected to be the basis for evaluation and continuous improvement in the management of B3 waste in the electricity generation industry to support the principles of sustainability and compliance with environmental regulations.